The Influence of Islamic Leadership, Organizational Culture, Organizational Climate and Work Behavior on Teacher and Employee Performance - Muhammad Idris Addayan; Robi Hendra (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of Islamic Leadership, Organizational Culture, Organizational Climate and Work Behavior on Teacher and Employee Performance at Al-Azhar Jambi, Bungo, and Tebo. Using descriptive quantitative research methods, data were collected from 310 teachers through questionnaires distributed online. Data analysis was carried out using the Smart-PLS 4 application, which allows for effective testing of relationships between variables. Islamic leadership has a positive and significant effect on teacher and employee performance. Organizational culture has a positive and significant effect on teacher and employee performance. Islamic leadership also has a significant positive effect on work behavior, with the Organizational Climate coefficient having a significant effect on work behavior. Work behavior shows a very strong and significant effect on teacher and employee performance.